Employee Primacy and Corporate Slogans in Japanese and American Firms' Communication in Times of Crisis. (January 2020) - Lehmberg, Derek; Tangpong, Chanchai
Given the frequency and severity of crises faced by organizations, the question of how managers can best lead their organizations through times of crisis is important. Communication plays a particularly critical role in such situations. We perform a multistage content analysis study using letters to shareholders appearing in publicly traded Japanese and U.S. firms during the economic downturn following Lehman Brothers bankruptcy in 2008. In our initial exploratory study, we identify employee primacy and the existence of corporate slogans as relevant constructs. We then develop hypotheses and test them in a larger sample confirmatory study. We find that firms concurrently exhibiting both employee primacy and corporate slogans in their communication outperformed their peers. To aid in interpreting our results, we also provided three examples of qualitative descriptions of such firms. Our Japanese and U.S. sample increases the generalizability of our results.